2019
DOI: 10.1161/hypertensionaha.118.12079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Automated Office Blood Pressure With Office and Out-Off-Office Measurement Techniques

Abstract: Automated office blood pressure (AOBP) has emerged as valuable tool to assess patient's blood pressure (BP) status, but the lack of strong evidences to establish a threshold value for hypertension diagnosis limits its use in clinical practice. We aimed at synthesizing the published literature through a meta-analysis of studies comparing AOBP with other BP measurement techniques and at analysing the differences between AOBP and physician's office BP, non-physician's office BP, daytime ambulatory BP monitoring (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 57 publications
(61 reference statements)
0
48
1
Order By: Relevance
“…Conversely, another commonly used outcome measure, office BP measurements, had higher variability in interventional trials on repeated measurements than ABPM [ 34 ]; and it was reported that SBP could drop more than 10 mmHg without intervention on repeated office BP measurements [ 35 ]. Recently, two published meta-analyses reported that a newer office BP measurement method, called the automated office BP measurement (AOBP), could provide similar mean SBP readings to daytime ABPM [ 15 , 36 ]. However, more data is needed to confirm if AOBP can be as reproducible as ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another commonly used outcome measure, office BP measurements, had higher variability in interventional trials on repeated measurements than ABPM [ 34 ]; and it was reported that SBP could drop more than 10 mmHg without intervention on repeated office BP measurements [ 35 ]. Recently, two published meta-analyses reported that a newer office BP measurement method, called the automated office BP measurement (AOBP), could provide similar mean SBP readings to daytime ABPM [ 15 , 36 ]. However, more data is needed to confirm if AOBP can be as reproducible as ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…An automated office blood pressure measurement (AOBPM), in which clinic BP is measured when patient is unattended sitting in a quiet room, might be an alternative if ABPM cannot be applied as for evidences from the recent meta-analyses (78,79) . These evidences showed that BP measured by AOBPM was not different from BP measured by awake/daytime ABPM, but it was significantly different when compared to CBPM which was measured by physicians or nurses.…”
Section: Discussionmentioning
confidence: 99%
“…An automated office blood pressure measurement (AOBPM), in which clinic BP is measured when patient is unattended sitting in a quiet room, might be alternative if ABPM cannot be applied as for evidences from the recent meta-analyses (65,66). These evidences showed that BP measured by AOBPM was not different from BP measured by awake/daytime ABPM but it was significant different when compared to CBPM that measured by physicians or nurses.…”
Section: Discussionmentioning
confidence: 99%